ДЎСТЛИККА КЎПРИК БЎЛГАН ИЖОД (Рустам Мусурмон ижоди мисолида) - Қурамбоева, Г. (SCIENCE and SOCIETY, 2023)
The article highlights the unique features of the work of Rustam Musurman, the national poet of Karakalpakstan, and his ability to create a national color in his poems on the subject of Karakalpakstan.